Bonhoeffer [compact disc, unabridged] : pastor, martyr, prophet, spy : a righteous gentile vs. the Third Reich - Metaxas, Eric (Blackstone Audio, 2010)
This is a groundbreaking biography of Dietrich Bonhoeffer, one of the greatest heroes of the twentieth century, the man who stood up to Hitler. A definitive, deeply moving narrative, Bonhoeffer is a story of moral courage in the face of the monstrous evil that was Nazism. After discovering the fire of true faith in a Harlem church, Bonhoeffer returned to Germany and became one of the first to speak out against Hitler. As a double agent, he joined the plot to assassinate the Führer and was hanged in Flossenbürg concentration camp at age thirty-nine. Since his death, Bonhoeffer has grown to be one of the most fascinating, complex figures of the twentieth century. Bonhoeffer presents a profoundly orthodox Christian theologian whose faith led him to boldly confront the greatest evil of the twentieth century and uncovers never-before-revealed facts, including the story of his passionate romance.